2018
DOI: 10.1111/head.13254
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Perspectives on the Burden of a Parent's Migraine: Results from the CaMEO Study

Abstract: Parental migraine negatively impacts adolescent children, extending our understanding of the family burden of migraine and emphasizing the potential benefit to children of optimizing migraine care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 27 publications
(59 reference statements)
1
29
0
Order By: Relevance
“…The reported impact was greatest in families of people with CM . For example, adolescent children of people with CM reported missing group and social activities and major events because of their parent's migraine/headache significantly more frequently than those with parents with EM . In a separate study, a higher frequency of migraine attacks was associated with a greater negative impact on the global well‐being of adolescent children of the proband and a greater impact on their personal future .…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The reported impact was greatest in families of people with CM . For example, adolescent children of people with CM reported missing group and social activities and major events because of their parent's migraine/headache significantly more frequently than those with parents with EM . In a separate study, a higher frequency of migraine attacks was associated with a greater negative impact on the global well‐being of adolescent children of the proband and a greater impact on their personal future .…”
Section: Introductionmentioning
confidence: 90%
“…Indeed, the impact of migraine on family life has been assessed in several studies demonstrating that migraine has adverse effects on family life and social/leisure activities of families, most notably on spouses and children . The effect of EM and CM on family life, particularly family activities and relationships, has been assessed in The Chronic Migraine Epidemiology and Outcomes (CaMEO) Study, including from the perspectives of spouses/domestic partners and adolescent children of those with migraine . People with migraine, as well as their partners/spouses, reported that headache/migraine had myriad negative effects on family life and family members .…”
Section: Introductionmentioning
confidence: 99%
“…Second, many teenagers with difficult headache disorders can become socially isolated due to their high headache‐related disability . Third, the burden of adolescent headache can also impact other family members, and family function seems to affect a child's experience of headache . Fourth, it is important equip teenagers with the skills they need in order to transition successfully into the adult health care environment (summarized in Table e in supporting information) …”
Section: Introductionmentioning
confidence: 99%
“…6,7 Emerging research suggests that the migraine also impacts the family of people with migraine. [8][9][10][11][12][13] The impact of migraine on the family is particularly important in this disease because the prevalence of migraine peaks between early and middle adulthood and then subsequently declines; this period is likely to correspond with family-related major life events, such as marriage and having children. Parenting in particular could be impacted by the unpredictable and disabling nature of migraine attacks.…”
mentioning
confidence: 99%
“…A 2004 online survey of 866 people with migraine and 162 family members without migraine found that almost half of the family members reported that living with or being related to a person with migraine had a moderate or great impact on home/family life (49.0%). 8 Recently, an analysis of data from adolescent respondents to the Chronic Migraine Epidemiology and Outcomes (CaMEO) Study 13 reported types and rates of impact of parental migraine on adolescent children (n = 1411; aged [13][14][15][16][17][18][19][20][21] living with the parent with migraine and evaluated differences reported between adolescents of parents with chronic (15 or more days/month) or episodic migraine (14 or fewer days/month) using a survey designed specifically to evaluate the family impact of migraine. Adolescents reported that migraine impacted parental support, their emotional experiences, school, and group activities; for example, 50.0% of adolescents of parents with chronic migraine, and 27.0% of adolescents of parents with episodic migraine reported they could not get help when they needed it from their parent with migraine at least once per month.…”
mentioning
confidence: 99%